2022
DOI: 10.1007/s11224-022-01981-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of nonlinear optical responses of phytochemicals of Clitoria ternatea by quantum mechanical approach and investigation of their anti-Alzheimer activity with in silico approach

Abstract: Clitoria ternatea is a flowering plant with promising medicinal plants with a wide variety of active phytochemicals. The present study aimed at the computational investigation of the nonlinear optical (NLO) responses of the active phytochemicals of the Clitoria ternatea. The computational investigation of the NLO features was done by using the density functional theory (DFT) by B3LYP/6-311G + + (d, p) basis set. The structural parameters, mulliken charge distribution, and molecular electrostatic potential (MEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Various natural compounds belonging to different chemical classes have been reported to exhibit inhibitory effects on acetylcholinesterase and butyrylcholinesterase enzymes. Several studies have demonstrated the potential of polyphenols as potent anti-cholinesterase agents [ 28 ]. In a recent study by Liu [ 20 ], the authors demonstrated significant anti-Alzheimer’s disease potential by testing a variety of bioactive compounds from A. membranaceus , which was also confirmed by molecular docking targeting the AChE enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Various natural compounds belonging to different chemical classes have been reported to exhibit inhibitory effects on acetylcholinesterase and butyrylcholinesterase enzymes. Several studies have demonstrated the potential of polyphenols as potent anti-cholinesterase agents [ 28 ]. In a recent study by Liu [ 20 ], the authors demonstrated significant anti-Alzheimer’s disease potential by testing a variety of bioactive compounds from A. membranaceus , which was also confirmed by molecular docking targeting the AChE enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular electrostatic potential (MEP) surface and counterplots were plotted for each combination to spot the moieties behaving as nucleophilic and electrophilic sites. The Koopman's set of identities mentioned below were used for calculating the global reactivity describing parameters band gap (ΔE), ionization potential (IP), electron a nity (EA), chemical potential (CP), electronegativity (χ), chemical hardness (η), softness (S), electrophilicity index (ω), electropositive index (ω + ), and electronegative index (ω − ) [26,27]:…”
Section: Methodsmentioning
confidence: 99%
“…But, the value of EA in the considered solvents was less as compared to the gas phase. The CP is the potential that a molecule has for the intra and intermolecular charge association [38]. The more negative value of CP shows the chemical activity of the complex as compared to the probe PABA.…”
Section: Molecular Orbitals Analysismentioning
confidence: 99%